Expanded non-invasive prenatal testing offers better detection of fetal copy number variations but not chromosomal aneuploidies - Shaozhe Yang; Yuan Zhuang; Junfeng Li; Xiuhong Fu (PLoS ONE, 2025)
Purpose To evaluate the clinical performance of expanded non-invasive prenatal testing (NIPT-plus) and compare its effectiveness in screening for chromosomal aneuploidies with that of NIPT. Methods Screening results, confirmatory invasive testing results, and follow-up data from pregnant women who underwent either NIPT (6792 cases) or NIPT-Plus (5237 cases) testing at Luohe Central Hospital, China, from January 2019 to June 2023 were collected. The positive predictive value (PPV), sensitivity, specificity, and other indicators for different types of chromosomal abnormalities in NIPT/NIPT-plus screening were calculated. The willingness of pregnant women with various types of abnormalities to undergo confirmatory invasive testing and the proportion of pregnancy terminations were investigated. Results The average number of unique reads in NIPT-plus samples was 5.26 times greater than that in NIPT samples. There was no significant difference in the PPV or positive rate between NIPT-plus and NIPT for screening chromosomal aneuploidies. Compared with the low-risk group, the high-risk group had a greater PPV; however, in the NIPT-plus group, there was no significant disparity in the PPV between the low-risk and high-risk groups. Compared with rare autosomal aneuploidies (RAAs), pregnant women had a higher rate of confirmatory invasive testing for common trisomies, sex chromosomal abnormalities (SCAs), and copy number variations (CNVs). However, the rate of pregnancy termination for common trisomies, RAAs, and CNVs was higher than that for SCAs. Conclusion By enhancing sequencing data, NIPT-plus can effectively screen for CNVs as well as chromosomal aneuploidies. However, NIPT-plus does not have an advantage over standard NIPT in screening for chromosomal aneuploidies.